Teores de nutrientes minerais e metais pesados em açúcar mascavo produzido por diferentes sistemas orgânicos e convencionais - Luchini, Paulo Dirceu (2014)
The levels of Cu, Zn, Mn, Fe, Pb and Cd were determined in brown sugar from sugar cane produced by different crop systems in the organic and conventional systems. Pb e Cd were determined by atomic absorption spectrometry with electro thermal atomization in graphite furnace (GFAA), and the mineral metals Cu, Zn, Mn and Fe were determined by flame atomic absorption spectrometry (FAAS). Cu, Zn, Mn and Fe were detected but in levels below the limits recommended by the World Health Organization. The brown sugar from the conventional system without limestone but with chemical fertilizer showed the highest concentration of Cu, Zn, Mn and Fe, and that from the organic system with liming and organic compost showed the lowest concentrations. The levels of Pb found in samples from: conventional system with organic amendment and chemical fertilizer, and with liming and chemical fertilizer, and from organic system with liming and organic compost were higher than the tolerable limit for the Brazilian National Health Surveillance Agency for sugar. Cd was never detected. The results indicate the need of constant monitoring studies of the brown sugar produced in organic systems to assure its food safety.